Synthesis of Aurivillius Phase CaBi4Ti4O15 Doped with both La3+ and Mn3+ Cations: Crystal Structure and Dielectric Properties - Zulhadjri,Zulhadjri (2020)
Abstract The four-layer Aurivillius CaBi4Ti4O15 with introducing of La3+ on the A-site and Mn3+ on the B-site with the formula Ca1-xBi3+xLaTi4-xMnxO15 (x = 0, 0.2, 0.4, 0.6, 0.8, and 1) were synthesized by molten salt method using the mixture of sulfate salts K2SO4/Na2SO4 as the flux. XRD data confirmed the formation of single-phase Aurivillius with A21am orthorhombic structure for x = 0, 0.2, 0.4, and 0.6, whereas for x = 0.8 and 1, the impurity phases were observed. SEM analysis shows the anisotropic plate-like grains, which are a typical grain of Aurivillius phases. The cell volume decreases with increasing x, indicating a presence of mixed valences of Mn3+ and Mn4+. The dielectric constants increased with x, strongly correlated with the higher distortion of the structure, the 6s2 lone pair electrons of Bi3+ cation increase. The presence of Mn3+ unpaired electrons results in the increase of dielectric loss as increasing x.